Comparison of the Efficacy of Intravitreal Aflibercept and Bevacizumab for Macular Edema Secondary to Branch Retinal Vein Occlusion - Wang, Jia-Kang (J Ophthalmol, 2016)
Fifty-two eyes of 52 patients with treatment-naïve macular edema associated with perfused branch retinal vein occlusion were retrospectively reviewed. Twenty-seven cases received PRN intravitreal bevacizumab, and 25 cases were treated by PRN intravitreal aflibercept with monthly follow-ups for 12 months. Both aflibercept and bevacizumab were effective in reduction of macular thickness and improvement of visual acuity for the participants. Both antivascular endothelial growth factor agents had similar efficacy and duration of treatment for these eyes with macular edema secondary to branch retinal vein occlusion during a 12-month period. No serious systemic or ocular adverse events were reported.